The nature, value and characteristics of lateral marketing in modern conditions - Bazarova, S.K.; Nabiev, E.N.; Shohamanova, A.M. (BUKETOV BUSINESS REVIEW, 2019)
Currently, marketing prerequisites are developing in several areas, adapting them to the new reality and modern features of the economy. There are additions to the marketing, new concepts that go beyond the boundaries of the axioms of classical marketing. One of the latest sensational marketing upgrades is the socalled lateral marketing. In the article the main provisions of the concept of lateral thinking are discussed. It is noted that lateral thinking is another attempt to create a scheme of creativity, a recipe for creating brilliant ideas. This is a set of schemes, rules for creative search for ideas. The definition of F. Kotler is given that lateral marketing is a working process that receives existing objects (goods or services) at the inlet and provides innovations (goods and services) at the outlet aimed at needs. The essence of lateral marketing is revealed, which consists in creating fundamentally new innovative products or services, new ideas, in the conditions of creating a new market and going beyond the limits of the old, existing one. The main goal of lateral marketing is to expand the scope of the marketing concept by developing a consistent process on which it is based, and to get ideas that consumers or marketing researchers cannot offer. The novelty of lateral marketing is emphasized, which consists in the fact that it creatively solves marketing problems, implements an innovative approach in relation to the elements of the marketing mix «4Р». Based on the use of sources, the authors identified the distinctive features of classical and lateral marketing, vertical and lateral marketing. It emphasizes the need for companies that do not occupy a leading position in the international market to use lateral marketing techniques. Investing in this innovation will bring the level of competitiveness of domestic enterprises to an acceptable level and ensure high rates of profitability.